Canon Law Manuscripts in the Medieval Abbey of St. Germain des Prés - Szuromi, Szabolcs Anzelm (Archiv für katholisches Kirchenrecht, 2016)
This work is an overview on those medieval canon law manuscripts which still testify the literary culture of the Benedictine Abbey of St. Germain des Prés. For the reconstruction of its original collection, have been used the material of two important libraries, i.e. Paris, Bibliothèque Nationale and the National Library of St. Petersburg. This description can give an outline on the original medieval library, focusing on its canon law material. The analyzed manuscripts testify not only the ownership by this very abbey, but a flourishing canon law activity in several fields of the ecclesiastical institutionalized life wherein they were used on the day-to-day basis. The several hands and many supplements or inscriptions show well the application of canonical norms for instruction, for cases at the ecclesiastical tribunal, for the interpretation of administration sacraments and sacramentals, particularly regarding the matrimonial and penitential service of the faithful.